Segregasi Sosial Pada Masyarakat Batak Toba dan Resolusinya Untuk Eksistensi Organisasi Sosial di Kota Medan - Harisan Boni Firmando (Jurnal Intervensi Sosial dan Pembangunan, 2023)
This study discusses social segregation in the Toba Batak community and its resolution for the existence of social organizations. This study aims to understand the causes of social segregation and the local wisdom values of the Batak Toba community that can create social integration. The method used in this research is a qualitative method with a descriptive approach. Data collection was carried out using observation techniques, interviews and focus group discussions so that conclusions can be drawn. The results in this study indicate that the social segregation that often occurs in the social organizations of the Toba Batak community can be divided into three aspects, namely; the dialectic of tarombo development, the dichotomy of the distribution of inheritance and claims to birthright. Efforts to reduce social segregation can be done with the dalihan na tolu kinship system approach which functions as a social institution. The presence of social organizations based on the dalihan na tolu kinship system is expected to be able to organize the attitudes of members of these social organizations and provide solutions to various social problems through deliberations and consensus of members.